Awareness of Medical Negligence among Practitioners - Sudharshan S1 , Magendrann. J2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction The cases of medical negligence in the recent years have been gradually increasing. Unless knowledge about medical negligence is strictly implicated in the medical practice the rate of medical negligence will increase. Nearly 50lakh Indians die due to medical negligence every year. Ain & Objective The present study was aimed to assess the level knowledge and awareness regarding medical negligence among medical practitioners . Materials & Method The present cross sectional study was conducted in saveetha medical college and hospitals , Chennai. A total of 100 practitioners were studied . The study period was from 24th February to 12th march 2019. Result ; In total , 100 medical practitioners were studied, of which almost all had knowledge about medico legal cases , only 88 of them take precautions during handling medico legal cases . only 47% were aware of the punishments given for medical negligence. Conclusion The awareness among the practitioners is satisfactory. But 37% of the practitioners couldn’t differentiate medical negligence from medical errors. The knowledge about the punishments given for an act of medical negligence is not satisfactory only ,40% had knowledge inn that area. The attitude of taking precautions during handling a medical legal case was satisfactory, only 12% of them don’t take precautions .